Alcohol consumption in university students. Case study: Espoch - school of mechanical engineering - Altamirano Balseca, Marco; Balseca Castro, Jaqueline Elizabeth (mktDESCUBRE; Vol 1 No 15 (2020): Fifteenth Edition (January - June), 2020)
Alcohol is a licit drug that becomes a public health problem with serious social consequences, its consumption has increased to the level of university students. At the country level there are few studies on the problems generated by consumption in students. In this study, use primary sources with the application of a questionnaire to students of the third semester of the School of Mechanical Engineering (ESPOCH), associated with sociodemographic variables and aspects of alcohol consumption. The outstanding findings that alcohol has increased in mostly male university students, who recognize that it is a legal drug, have consumed it on occasion in order to feel accepted in a fun social environment and to escape from problems. personal and uncontrolled emotions. In this sense, it is possible to work in a timely manner in information, prevention and control programs for alcohol consumption in students of the first levels of university who are probably the most likely to acquire the habit of drinking without any control, especially when their performance Academic is an essential and fundamental factor for the evaluation of educational quality in higher education.